1999
DOI: 10.1144/petgeo.5.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Litho-flow facies prediction in an alluvial fan/fluvial system, central North Sea

Abstract: An existing generic facies scheme consisting of a channel, sheetflood and floodplain facies was available from the cored wells. Bivariate and multivariate analysis of various wireline and core data indicated that each generic facies exhibits wide variations and significant petrophysical overlap with other facies. This scheme cannot therefore reliably be applied using wireline data, negating its application in uncored intervals through discriminant analysis. Due to the large variation in porosity and permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are many practical problems with this approach: for example, quantifying uncertainty, dealing with qualitative data, appropriate definition of facies and calibration of resulting models (e.g. Wong et al 1997;Vaughan et al 1999;Biver et al 2002;Liu & Oliver 2005;Martinius & Naess 2005). Nevertheless, codes that include explicit accounts of bedforms and facies are starting to be used not only in research but also in practical applications (e.g.…”
Section: T H E P R E S E N T -D a Y S A N D S T O N E S E Q U E N C Ementioning
confidence: 99%
“…There are many practical problems with this approach: for example, quantifying uncertainty, dealing with qualitative data, appropriate definition of facies and calibration of resulting models (e.g. Wong et al 1997;Vaughan et al 1999;Biver et al 2002;Liu & Oliver 2005;Martinius & Naess 2005). Nevertheless, codes that include explicit accounts of bedforms and facies are starting to be used not only in research but also in practical applications (e.g.…”
Section: T H E P R E S E N T -D a Y S A N D S T O N E S E Q U E N C Ementioning
confidence: 99%
“…Using the six‐fold facies classification scheme (Table 3), between five and 10 samples were taken from each facies type to characterise their grain size distribution and ensure that the grain size distribution accounted for intra facies variation, which has been recognised as important in previous field studies (e.g. Dreyer et al ., 1990; Vaughan et al ., 1999).…”
Section: Facies Type and Grain Size: Estimation Of Hydraulic Conductimentioning
confidence: 99%
“…Porosity and permeability are probably the most important quantifiable controls in reservoir fluid flow simulations and studies have shown that they are primarily a function of grain size and sorting (Freeze & Cherry, 1979; Brayshaw et al ., 1996; Robinson & Friedman, 2001), sedimentary structure (Scheibe & Freyberg, 1995) and diagenesis (Jacobson & Rendall, 1991; Hornung & Aigner, 1999). Many studies assume that the permeability distribution in an alluvial deposit is a function of sedimentary facies and depositional process (Alexander, 1993), and thus the link between petrophysical properties and fluvial sedimentology has been made in deposits from both reservoir wells (Begg et al ., 1989; Atkinson et al ., 1990; Lui et al ., 1996; Eschard et al ., 1998; Tye et al ., 1999; Vaughan et al ., 1999) and outcrop (Ravenne & Beucher, 1988; Dreyer et al ., 1990; Miller et al ., 1990). Clearly, there is an untapped potential for using aggrading physical models of alluvial sedimentary basins to provide information on the spatial distribution and geometry of different sedimentary facies and then relate this to the petrophysical properties.…”
Section: Introductionmentioning
confidence: 99%